Econometric Properties of Asset Valuation Rules Under Price Movement and Measurement Errors: An Empirical Test. - Hall, Thomas W.; Shriver, Keith A. (The Accounting Review, 1990)
Evaluates several analytical results developed in earlier studies and investigates the absolute econometric properties of valuation rules using date from a specific economic environment. Statistical theory of valuation; Effects of valuation error on current cost data; Relationship between portfolio diversification and valuation error.